Cs4PbI6‐Mediated Synthesis of Thermodynamically Stable FA0.15Cs0.85PbI3 Perovskite Solar Cells. Issue 30 (21st June 2020) - Shao, Zhipeng; Meng, Hongguang; Du, Xiaofan; Sun, Xiuhong; Lv, Peiliang; Gao, Caiyun; Rao, Yi; Chen, Chen; Li, Zhipeng; Wang, Xiao; Cui, Guanglei; Pang, Shuping
Abstract: The stability issue is still one of the main limitations of the commercialization of perovskite photovoltaics. The mixed cation FA x Cs1 −x PbI3 has shown great promise owing to its improved thermal and moisture stability. However, the study of FA x Cs1 −x PbI3 is concentrated on formamidine (FA)‐rich perovskite, whereas cesium (Cs)‐rich FA x Cs1 −x PbI3 perovskites are barely studied due to the inevitable phase separation when Cs > 30 mol%. Here, a Cs4 PbI6 ‐mediated method is developed to synthesize Cs‐rich FA x Cs1 −x PbI3 perovskites. It is demonstrated that Cs4 PbI6 intermediate phase has a low Cs cation diffusion barrier and therefore offers a fast ion exchange with the preformed FA‐rich perovskite phase to finally form the Cs‐rich FA x Cs1 −x PbI3 perovskite. The results indicate that ≈15% alloying with organic FA cations can sufficiently stabilize the perovskite phase with excellent phase and UV‐irradiation stability. The FA0.15 Cs0.85 PbI3 perovskite solar cells achieve a champion power conversion efficiency of 17.5%, showing the great potential of Cs‐based perovskites for efficient and stable solar cells. Abstract : A Cs4 PbI6 ‐mediated method is developed to fabricate cesium (Cs)‐rich perovskite films. It is also found that ≈15% alloying with the organic formamidine (FA) cation can sufficiently stabilize the perovskite phase with excellent phase and UV‐irradiation stability. FA0.15 Cs0.85 PbI3 ‐based perovskite solar cells achieve a champion power conversion efficiency of 17.5%.